Translation and psychometric evaluation of the Chinese version of the Mathematical Resilience Scale - Wang, Xia; Amalia, Madihie; San Nah, Sze (Elsevier B.V., 2025)
The translation of the Mathematics Resilience Scale (MRS) into Chinese provides an essential tool for educational research within Chinese cultural contexts, and this study supports educators in identifying emotional and cognitive barriers that students encounter in mathematics learning, thereby enabling targeted interventions. This study focuses on translating the MRS into Chinese and evaluating its reliability and validity within the Chinese context. The translation adhered to Beaton et al.'s (2000) guidelines, with validity and reliability assessed through item analysis, reliability analysis, validity analysis, item response theory, and differential item functioning. The Cronbach's α value for the MRS was .969, indicating strong performance, while item factor loadings ranged from .514 to .859, and the Kaiser-Meyer-Olkin value was .968. The Chinese version of the MRS has been accurately and thoroughly translated, demonstrating robust psychometric properties. This study provides a quantitative instrument for addressing resilience-related issues in mathematics education, offering valuable data to inform interventions for policymakers and educators. The study significantly contributes to ensuring the cross- cultural applicability and validity of the MRS, offering a reliable tool for international research on mathematical resilience.